Az Zawaaj Al Urfi Al Gorontalowy Fi Mandzuuri As Syariah Al Islamiyah - Abubakar, Luqmanul Hakim, Dr. Muinudiniah Basri, MA, Dr. Khairuddin Kamsen, MA (2017)
This thesis is applied for Islamic Law Master Program, Muhammadiyah University of Surakarta. Arranged by: Luqmanulhakim Abubakar. NIM: O 000110025. Under the supervision of: Dr. Muhammad Mu'in Dinillah Bashri, MA and Dr. Muhammad Khairuddin Hamsin. Year : 2017 AD - 1438 H. This thesis researched about Gorontalo tradition marriage law in the perspective of Islamic law, and the research includes three points: (1) What is the tradition and how to be considered in the construction of regulation (2) how the system of marriage tradition in Gorontalo (3) what are the approval and the offense between Gorontalo tradition marriage and Islamic jurisprudence? After searching and looking at a number of sources and references, the researcher concluded: (1) that the tradition in the perspectiveof islamic law has an important role, for many practical judgments among the people in various of Fiqh and its chapters, so it has not independent evidence in Islamic Law, but it has to be returned to the basic of the basic fundamentals of Islamic law: Sunnah, Ijma', the public interest, and permissibility 2) The general text in the family regulation in Gorontalo is derived from Islamic law. So we must abide by all the regulation. (3) But the problem through research and investigation, we found that some of the material which circumvent Islamic law, such as the prevention of marriage agreement in the certain days and months, and increases to the conditions in which to be burdened. so It is necessary to raise this problem by giving a statement that correct or contrary to Islam and perhaps it be useful guidance to return to a pure source Key word: Marrriage, Tradition, Islamic law, Gorontalo